Medical image computing and computer assisted intervention -- MICCAI 2018. 21st International Conference, Granada, Spain, September 16-20, 2018, Proceedings /: 21st International Conference, Granada, Spain, September 16-20, 2018, Proceedings. Part IV : (2018) - Unknown
No abstract available